Botany, traditional uses, phytochemistry, pharmacology and toxicology of Ilex pubescens Hook et Arn. (5th December 2019) - Jiang, Shiqin; Cui, Hui; Wu, Peng; Liu, Zhongqiu; Zhao, Zhongxiang
Abstract: Ethnopharmacological relevance: Ilex pubescens ( I. pubescens ), which is well known in Chinese as Mao-Dong-Qing, is widely used in traditional Chinese medicine. This plant is distributed in the wild in southern China, and the roots and stems are used for clearing heat, detoxifying, activating blood circulation and dispelling stasis. Moreover, it is used for treating wind-heat cold, lung-heat asthma, swelling and pain of pharynxes and gingivae, thoracic obstruction and cardiodynia with pungent, stroke, hemiplegia, thromboangiitis obliterans, burn, scald and central retinitis. Aims of the review: This paper aims to provide a critical summary of the current studies on I. pubescens . The progress in research on the botany, traditional uses, phytochemistry, pharmacology and toxicology of the plant is discussed. We mainly focus on the phytochemical and pharmacological investigations of I. pubescens . Furthermore, perspectives for possible future studies on I. pubescens are also discussed. Materials and methods: A systematic review was conducted on the studies of I. pubescens performed during the past 40 years with resources including the Chinese Pharmacopoeia and literature databases such as PubMed, Science Direct, Wiley, CNKI (China National Knowledge Infrastructure), SciFinder, Web of Science, Google Scholar and Baidu Scholar. Results: To date, more than 200 compounds have been isolated and identified from the plant, a substantial proportion of which were reported to be triterpenes. Biological effects such as protective effects against cardio-cerebrovascular diseases, anti-thrombosis, anti-inflammatory and anti-tumour activities were also investigated in in vitro and in vivo research. Therapeutic effects are attributed to the bioactivities of the naturally occurring compounds in this herb. Furthermore, toxicological studies on I. pubescens are relatively scarce, and it is worthy of further research. Conclusions: This review summarizes the results from current studies of I. pubescens, which is one of the valuable medicinal sources from traditional herbs. Some conventional uses have been evaluated by pharmacological investigation. In addition, unresolved issues include molecular mechanisms underlying bioactivities, pharmacokinetics, toxicology and efficacy, which are still being studied and explored before achieving integration into clinical medicines.